Viabilidade de sementes de Passiflora edulis Sims. f. flavicarpa Deg - Lima, Paula Aparecida Muniz de (2019)
The quality of the seed is extremely important for the conduct of a crop and the storage conditions are fundamental in preserving its quality. In view of the above, the objective is to study the viability of seeds of Passiflora edulis Sims. f. flavicarpa Deg. with different water contents, the physiological quality of seeds of passion fruit hybrids cultivated at three altitudes and the behavior of these seeds stored in a cold room and natural environment. For the evaluation of the physiological quality of the seeds during storage, yellow passion fruit seeds with adjusted humidity levels were used: 10; 14; 18 and 22%, which were stored in plastic bags of 0.10 mm thickness and stored in a cold room at 4 °C and in a natural laboratory environment 25 ± 2 °C. In order to study the physiological quality of passion fruit hybrids stored in cold rooms and in the natural laboratory environment, hybrids were used: BRS Gigante Amarelo, BRS Sol do Cerrado and BRS Rubi do Cerrado, grown at three altitudes in the state of Espírito Santo (104 711 and 1016 meters). The variables studied were: seed water content, germination, germination speed index, shoot length, root length and dry mass of the seedlings. Yellow passion fruit seeds stored in a cold room and in a natural environment with 14% moisture present higher physiological quality during eight months (240 days) of storage. Seeds of yellow passion fruit stored in cold room and natural environment present maximum germination and vigor after 60 days of storage. The seeds of yellow passion fruit are orthodox and must be stored at 14% humidity, in a cold room and in a natural environment, without loss of viability and physiological quality for eight months (240 days), presenting maximum germination and vigor after 60 days without the presence of pathogens. Seeds of hybrids of Passiflora edulis Sims. f. flavicarpa Deg. can be stored in a natural environment or cold room. Seeds of hybrids of Passiflora edulis Sims. f. flavicarpa Deg. originating from altitudes of 104 and 711 meters present higher percentages of germination and vigor. Seeds of the hybrid Giant Yellow showed lower averages for the variables studied, regardless of the altitude of origin. Seeds of the hybrid Rubi do Cerrado from an altitude of 1016 meters have a higher percentage of germination and vigor and can be stored for 180 days in a natural environment or cold chamber without loss of viability. Seeds of the hybrid Sol do Cerrado, originating from the altitudes of 104 and 711 meters, present higher percentages of germination and vigor, and can be stored for 180 days in a natural environment or cold chamber without loss of viability.